The current RIM landscape: findings from the 2018 RIM survey with an insigth into national CRIS systems - de Castro, Pablo (2018)
University of Strathclyde in GlasgowEstablished 1796 as “the place for useful learning”21,470 FTE Students and 3,200 staffResearch: research grants and contracts income of £59,921m in 2016Among the 20 top research-intensive universities in the UKPreviously— OpenAIRE2020 WP coordinator at LIBER (Assoc of European Research Libraries)in The Hague, the Netherlands— EDINA National Data Centre, University of Edinburgh, UK— Consejo Superior de Investigaciones Científicas (CSIC), Universidad Carlos III Madrid (UC3M), Spain